Impact of Retinal Vein Occlusion on Stroke Incidence: A Meta‐Analysis - Li, Min (J Am Heart Assoc, 2016)
BACKGROUND: Considerable controversy exists on the association between retinal vein occlusion (RVO) and stroke risk. Therefore, we conducted a meta‐analysis to assess the relationship between RVO and stroke risk. METHODS AND RESULTS: PubMed, EMBASE, and the Cochrane library databases were searched for cohort studies with data on RVO and stroke risk. Studies that reported adjusted relative risks (RRs) with 95% CIs of stroke associated with RVO were included. Stratified analyses were conducted according to key characteristics. A total of 5 articles including results from 6 prospective cohort studies with 431 cases of stroke and 37 471 participants were included in the meta‐analysis. Overall, after adjustment for established cardiovascular risk factors, participants with RVO at baseline were considerably more associated with a greater incidence of stroke risk (combined RR: 1.50, 95% CI: 1.19–1.90), compared to participants without RVO. The results were more pronounced for stroke (RR: 1.72, 95% CI: 1.24–2.37) in the stratified with a stroke history. The risk of stroke was nonsignificant in male subjects (RR: 1.20, 95% CI: 0.96–1.49) and in female subjects (RR: 0.93, 95% CI: 0.64–1.34). The presence of both central RVO (RR: 1.90, 95% CI: 1.46–2.48) and branch RVO (RR: 1.79, 95% CI: 1.18–2.72) was associated with increased risk of stroke. Stratifying by age, the associations between RVO and risk of stroke were similar between the age range in the cohorts that ranged from 50 to 59 years and 60 to 69 years. CONCLUSIONS: Exposure to RVO was associated with an increased risk of stroke, especially in subjects aged between 50 and 69 years. Future studies on the effect of RVO treatment and modifiable risk factor reduction on stroke risk in RVO patients are warranted.